Synthesis and characterisation of macrocyclic ligands with hydroxyalkyl and thiol pendant arms tethered on 1,5,9-triazacyclododecane and their complex formation chemistry - Sumani, Jimmy Ephet Yafeti (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2010.